Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12981-021-00374-8
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use HIV pre-exposure prophylaxis and associated factors among men who have sex with men in Liuzhou, China

Abstract: Background HIV pre-exposure prophylaxis (PrEP) is a key component of HIV combination prevention strategies and has the potential to decrease the incidence of HIV in men who have sex with men (MSM). This study aimed to evaluate levels of PrEP acceptability and explore factors associated with willingness to use PrEP among MSM in Liuzhou, China. Methods Between November 2017 and May 2019, a cross-sectional survey was conducted among 829 MSM. The study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…However, a better educational background was found to be negatively associated with the willingness to use LAI-PrEP in our study. This result contradicts previous studies showing that MSM with higher education levels had a higher willingness to use PrEP [ 61 , 75 , 76 ]. When our survey was conducted, LAI-PrEP was still under clinical trial and had not been approved both in China and other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a better educational background was found to be negatively associated with the willingness to use LAI-PrEP in our study. This result contradicts previous studies showing that MSM with higher education levels had a higher willingness to use PrEP [ 61 , 75 , 76 ]. When our survey was conducted, LAI-PrEP was still under clinical trial and had not been approved both in China and other countries.…”
Section: Discussioncontrasting
confidence: 99%
“…Tang et al demonstrated that an innovative crowdsourcing approach was effective for developing and strengthening community-based HIV testing services for MSM (15). Integrating social media with the distribution of self-test kits also holds promise to increase HIV testing coverage and case identification among MSM (16).…”
Section: Combination Prevention Hiv Risks and Prevention In Msmmentioning
confidence: 99%
“…However, less than one thousand were regularly taking PEP and even fewer taking PrEP. The awareness of and willingness to use PrEP and PEP among MSM was still extremely low ( 17 - 18 ). The probable barriers were the high price of PrEP (69.9%), the need to use condoms consistently (52.7%), concerns about side effects (39.8%), and concerns about effectiveness of prevention (22.6%) ( 18 ).…”
Section: Combination Preventionmentioning
confidence: 99%
“…From 2010 to 2020, there were about 10,000 newly diagnosed HIV infections and 5,000 AIDS-related fatalities each year in Guangxi, ranking first in the morbidity and mortality rate of HIV in China [ 19 , 20 ]. Liuzhou, in Guangxi Province, has the highest rate of HIV infection [ 21 ].…”
Section: Introductionmentioning
confidence: 99%